Conflict and poverty in Afghanistan's transition - Vincent A. Floreani; Gladys López Acevedo; Martín Rama (Institute of Labor Economics (IZA), 2019)
Despite record economic growth in the decade that followed the fall of the Taliban regime, poverty remained stubbornly high in Afghanistan, and especially so in regions that suffered less from conflict. This paper aims to explain this puzzle by combining a model of conflict intensity at the province level in 2007−14 with a model of consumption at the household level in 2011. The estimates show that large troop deployments reduced conflict intensity but also boosted local consumption, an effect reinforced by foreign aid flows being larger in conflict-affected areas. Out-of-sample simulations suggest that declining international troops and foreign aid after 2014 would lead to an increase in conflict intensity and a decline in consumption per capita, two trends validated by independent data sources.
Keywords: D74; E21; F35; I32; O17; 330; Afghanistan; conflict; poverty; foreign aid; troops; growth